2019
DOI: 10.1002/ptr.6568
|View full text |Cite
|
Sign up to set email alerts
|

The effect of l‐carnitine supplementation on serum levels of omentin‐1, visfatin and SFRP5 and glycemic indices in patients with pemphigus vulgaris: A randomized, double‐blind, placebo‐controlled clinical trial

Abstract: Pemphigus vulgaris (PV) is a chronic autoimmune disorder with potentially fatal outcomes. The aim of this study was to investigate the effect of l‐carnitine (LC) on secreted frizzled‐related protein‐5 (SFRP5), omentin, visfatin, and glycemic indices in PV patients under corticosteroid treatment. In this randomized, double‐blind, placebo‐controlled clinical trial, 52 patients with PV were divided randomly into two groups to receive 2 g of LC or a placebo for 8 weeks. Serum levels of SFRP5, omentin, visfatin, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…A total of 78 studies were excluded due to the following reasons: insufficient outcome data reported, acute oral ingestion, or short duration of supplementation (<1 week). Finally, we included a total of 41 studies ( 16 , 17 , 23 , 43 80 ) with 44 effect sizes included in the qualitative synthesis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 78 studies were excluded due to the following reasons: insufficient outcome data reported, acute oral ingestion, or short duration of supplementation (<1 week). Finally, we included a total of 41 studies ( 16 , 17 , 23 , 43 80 ) with 44 effect sizes included in the qualitative synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…The daily dosage of L-carnitine supplementation ranged from 0.25 to 4 g/day. 39 parallel ( 17 , 23 , 43 68 , 70 80 ) and 2 cross-over ( 16 , 69 ) studies were included in this study. The mean age ranged from 18–101 years and baseline BMI of included studies ranged from 22.19 to 36 kg/m 2 in the intervention group, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations